ANALISIS POTENSI LOKAL UNTUK PERENCANAAN PEMBANGUNAN DI KECAMATAN GUNEM - Tahwin, Muhammad (STIE YPPI Rembang, 2013)
This study aims to determine the potential map that expected to give the direction for development program policy in Gunem District. The method used in this study is regional approach with SWOT analysis. The result of the study show that Gunem has potential commodities of corns, mangoes,banans and cows. Based on socio-cultural potency, Gunem has large population. In economic, there are many businesses in the form of home industries. The human resources potency shows that Gunem society has high motivation to reach education and large amount of productive labor. The development program is carried out to improve the productivity of commodities, able to suppress the population growth, suport the business development, and the program is oriented in increasing societyâs knowledge and skill that support to be advanced intelligent and skilled people.Â Key words: development planning and program, SWOT analysis.